Education Park Concept on Green Open Space Planning through Historical and Cultural Approach - Sri Maqfirah Asyuni; Ahmad Syarief Iskandar; Nuryani Nuryani; Edhy Rustan (Institut Seni Indonesia Yogyakarta, 2022)
Green Open Space Planning (RTH) for urban areas needs to support ecological functions, education facilities, and social interaction facilities for urban communities and regional identity. As green open spaces, Complex Elementary Park and Reading Park in Palopo, South Sulawesi have not yet fulfilled their functions and benefits optimally. The two parks that are located in the heritage area become a unique/distinctive potential to show the historical connotation of the location in its design. This study aims to provide landscape design recommendations by exploring the potential of the location through the historical and cultural approach of the Luwu Kingdom. The research was conducted using a descriptive qualitative method that refers to the landscape planning of Seymour M. Gold through the stages of preparation, inventory, analysis, synthesis, and planning. The results of this study resulted in an Education Park site plan that elaborated the physical and philosophical characteristic of three cultural heritages, namely the Datu Luwu Palace Complex, the Jami' Mosque, and the Post and Giro Office. Konsep Taman Edukasi pada Perencanaan Ruang Terbuka Hijau melalui Pendekatan Sejarah dan Budaya. Perencanaan Ruang Terbuka Hijau (RTH) Kawasan Perkotaan perlu menunjang fungsi ekologis, wadah pendidikan, sarana interaksi sosial masyarakat urban dan identitas daerah. Sebagai RTH, Taman SD Kompleks dan Taman Baca di kota Palopo, Sulawesi Selatan belum menunjukkan terpenuhinya fungsi dan manfaatnya secara optimal. Kedua taman yang berada dalam kawasan heritage menjadi potensi khas/unik untuk menunjukkan historical connotation lokasi dalam desainnya. Penelitian ini bertujuan membuat rekomendasi desain lanskap dengan mengeksplorasi potensi lokasi melalui pendekatan sejarah dan budaya Kerajaan Luwu. Penelitian dilakukan menggunakan metode kualitatif deskriptif yang mengacu pada perencanaan lanskap Seymour M. Gold melalui tahapan persiapan, inventarisasi, analisis, sintesis dan perencanaan. Hasil penelitian ini menghasilkan siteplan Taman Edukasi yang mengelaborasi karakter fisik dan filosofis tiga cagar budaya yaitu Kompleks Istana Datu Luwu, Masjid Jami’ dan Kantor Pos dan Giro.